2013
DOI: 10.1371/journal.pone.0074545
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Oral Health Systematic Reviews Published 1991–2012: Cross Sectional Study

Abstract: ObjectivesTo identify all systematic reviews (SRs) published in the domain of oral health research and describe them in terms of their epidemiological and descriptive characteristics.DesignCross sectional, descriptive study.MethodsAn electronic search of seven databases was performed from inception through May 2012; bibliographies of relevant publications were also reviewed. Studies were considered for inclusion if they were oral health SRs defined as therapeutic or non-therapeutic investigations that studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 26 publications
6
37
0
Order By: Relevance
“…These figures are in keeping with a large survey of the Cochrane Database of Systematic Reviews involving analysis of 2,321 systematic reviews which highlighted a median of 6 meta-analyses per review and a median of 3 studies per meta-analysis [ 29 ]. A similar previous review [ 30 ] of dental systematic reviews reported a median of 9 studies were included in the largest meta-analysis within dental systematic reviews involving 9 dental specialties, with the largest meta-analysis having no more than 4 studies in 19% of reviews. Similarly, the largest meta-analysis involved a median number of just two randomized clinical trials, although that review referred back to systematic reviews from as long ago as 1991 when randomized clinical trials were considerably less prevalent in oral health than is now the case.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are in keeping with a large survey of the Cochrane Database of Systematic Reviews involving analysis of 2,321 systematic reviews which highlighted a median of 6 meta-analyses per review and a median of 3 studies per meta-analysis [ 29 ]. A similar previous review [ 30 ] of dental systematic reviews reported a median of 9 studies were included in the largest meta-analysis within dental systematic reviews involving 9 dental specialties, with the largest meta-analysis having no more than 4 studies in 19% of reviews. Similarly, the largest meta-analysis involved a median number of just two randomized clinical trials, although that review referred back to systematic reviews from as long ago as 1991 when randomized clinical trials were considerably less prevalent in oral health than is now the case.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, a considerable increase in SRs has been noticed [4], including in dentistry [5,6]. However, Page et al [4] along with Ioannidis (2016) [7] observed that the increase of such publications was accompanied by an increase of poorly conducted, reported and/or unnecessary SRs.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a vast number of SRs had been published in recent years, all of the varying quality 3‐6 . Thus, graduate programs should set guidelines for SR use in a master or PhD thesis in order to avoid “empty reviews.” Further, graduate programs must encourage researchers and students to be trained in all methodological aspects, including high‐quality SRs.…”
Section: Discussionmentioning
confidence: 99%
“…In dentistry, the same trend exists. Saltaji et al 5 found that 1 188 SRs were published between 1991 and 2012, while Bassani et al 6 stated that 495 SRs were indexed in the PubMed database in 2017.…”
Section: Introductionmentioning
confidence: 99%